Expulsion in futsal: Goals occurrence in games that have numeric superiority or inferiority of players - Leão, Douglas Xavier (2012)
Indoor Futsal is one of the most practiced sports in Brazil. Since it was born in the 30 ́s many changes in regard to procedure rules took place. According to rule 11 -Free kick and Incorrections; when a participant player is expelled from the game, the team will have one less player for a while. Within 2 minutes another player may replace the one who left. When the team in majority of players scores a goal, the other team will be allowed to be recovered with another player immediately. When the team with the lowest number of players scores a goal, player replacing will not be permitted. This study was developed aiming at quantifying the incidence of goals in Brazilian futsalmatches in non-professional and professional competitions, either with man team or woman team, to check how often teams take advantages of numerical superiority, check if goals take place within the first or second minute after the player expulsion, identify in which quarter of time player expulsion mostly happen and if there is any relation between the winner team and the team which was with one less player. The methodology used in this study was the study of match emulates of the 9th2009 Paquetá Sports Adidás Soccer Indoor Cupfor Students -Masculine and Feminine. And in the statewide-RS emulates Sub-11, Sub-13, Sub-15, Sub-17, Sub 20 Masculine and Feminine adult. Expulsions took place most frequently in the last match quarter and almost every goals happened up to 2 minutes after the expulsion; the biggest incidence of goals was of the team with higher number of players; in most cases, the team in numerical superiority was in advantage at the moment of the expulsion, goals took place most frequently just after the player expulsion. This study concluded that numerical superiority caused by players expulsion at the opponent team has been profitable. Expulsions occur most frequently in teams in disadvantage in regard to scores and at the end of the match, making the team in numerical superiority enlarge the number of goals or just hold the time and keep results. However, there is not a specific formula to forecast these results. Futsalis unpredictable and everything may happen among the four lines, what makes this sport even more enjoyable and makes us willing to study more about it.